Can consumption make you happy? exploring student’s quality of Life from marketing perspective - Jan, Muhammad Tahir; Zain, Osman M.; Jehangir, Muhammad (Management Journals, 2011)
This present study explored the concept of quality of life (QOL) marketing from the perspective of students. Furthermore, it generated qualitative data which will open doors for future research in the same area. This study adopts a qualitative approach, using in-depth face-to-face interviews. A total of twenty participants were selected from different faculties currently residing in Malaysia and Pakistan. Several procedures were applied to carry out a rigorous qualitative analysis (i.e., interview guide, audio/ video recording and field notes, prompt transcription, coding and tabulating the transcripts, direct quotes and rich data slices when presenting findings). The findings of this paper revealed that in milieu of consumption students believe that their quality of life enhance with the consumption of various products. Further, for most of the students a strong relationship with their families and loved ones is an important factor of their quality of life. Country-based population studies should be carried out in order to assess and monitor the quality of life in a standard way. Further given that this research is qualitative, there is a need to embark on empirical data gathering on the same topic. This study was conducted in Malaysia and Pakistan, where no study has been conducted to explore the quality of life marketing from student’s perspective. Moreover, Consumption, an important facet of marketing, was also explored for the first time in the QOL context.